Translation Analysis Of Compound Sentence In Mitch Albom's Novel : The First Phone Call From Heaven Into Telepon Pertama Dari Surga By Julanda Tantani - Yalo, Masolaeh; , Dr. Anam Sutopo, M.Hum; , Mauly Halwat Hikmat, Ph. D (2015)
The research paper studies about the translation variation of compound sentence in Mitch's Albom novel The first Phone Call from Heaven. The study aims at classifying the types of sentences which are translated from the compound sentence, classifying the techniques used by the translator in transferring the compound sentence. The research paper is descriptive qualitative research. The object of the study is compound sentence in Mitch's Albom novel The first Phone Call from Heaven and its translation Telepon Pertama dari Surga by Julanda Tantani. The data are translation variation of compound sentence and the techniques used by the translator in transferring the source language. The data are collected from both books by using documentation method. The researcher applies comparison in analyzing the data of the study. The results of the research show that first, compound sentences are translated into 3 type of sentences. From 160 data, there are 149 data or 93,12% of compound sentence translated into compound sentence, 7 data or 4,37% of compound sentence translated into complex sentence, 4 data or 2,5% of compound sentence translated into simple sentence. Second, the researcher found 9 techniques used by the translator in transferring the source language. From 160 data, there are 86 data of pure borrowing, 14 data of naturalized borrowing, 25 data of addition, 4 data of generalization, 1 data of amplification, 7 data of particularization , 8 data of modulation, 39 data of transposition and 1 data of reduction.